Effect of icotinib on advanced lung adenocarcinoma patients with sensitive EGFR mutation detected in ctDNA by ddPCR - Chen, Hua-Fei; Lei, Lei; Wu, Li-Xin; Li, Xiao-Feng; Zhang, Qu-Xia; Pan, Wei-Wei; Min, Yong-Hua; Zhu, You-Cai; Du, Kai-Qi; Wang, Min; Wang, Wen-Xian; Xu, Chun-Wei (Translational Cancer Research; Vol 8, No 8 (December 31, 2019): Translational Cancer Research, 2019)
Background: Whether or not EGFR mutation status detected by ddPCR in plasma predicts the effect of icotinib on patients with advanced lung adenocarcinoma was determined. Methods: Plasma and matched tissue specimens from patients with advanced lung adenocarcinoma were collected prior to icotinib treatment. The ARMS method was used to detect EGFR mutation status in DNA extracted from tissue specimens, while the EGFR mutation status in ctDNA extracted from plasma specimens was determined by ddPCR. The therapeutic effects of icotinib were compared between patients with EGFR- activating mutations detected by ddPCR in ctDNA and ARMS in tissue DNA. Results: EGFR mutation status was detected in 96 tissue and 100 plasma specimens. The sensitivity and positive predictive value of 19del detected in ctDNA by ddPCR was 70.97% (22/31) and 44.90% (22/49), respectively. The positive predictive value was 84.62% (22/26) and the sensitivity was 53.66% (22/41) for the L858R mutation. For the common sensitive EGFR mutations, ddPCR had a positive predictive value of 77.19% (44/57) and a sensitivity of 48.89% (44/90). Patients with sensitive EGFR mutations in ctDNA had objective response and disease control rates (DCR) similar to patients who had sensitive EGFR mutations in tissues detected by ARMS when treated with icotinib (57.14% vs. 51.51% and 92.86% vs. 90.91%, respectively). Conclusions: Patients with sensitive EGFR mutations in plasma specimens detected with ddPCR had a higher ORR and DCR compared with patients with sensitive EGFR mutations in tissue detected with the ARMS method.